The influence of gibberellic acid (GA₃) for berry thinning and berry sizing on table grape production, quality and fertility of Prime - Van der Vyver, L. (Stellenbosch : Stellenbosch University, 2016)
Thesis (MScAgric)--Stellenbosch University, 2016.